2020
DOI: 10.1088/1755-1315/412/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Karst Groundwater Vulnerability and Risk to Pollution Hazard in the Eastern Part of Gunungsewu Karst Area

Abstract: Karst landscape generally has a high vulnerability to pollution. Karst landscape is a landscape that forms from soluble rock. The solution processes results many holes which connecting the surface to underground river networks. Soil and vegetation are generally thin and sparse. The increasing of the population and they various activities can add pressures to the landscapes such as in the eastern parst of Gunungsewu. The karst groundwater management and protection effort need its intrinsic vulnerability and ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Second, the anthropogenic activities factor mainly refers to the agricultural degree, industrial water discharge and groundwater exploitation. According to the study of the eastern part of Gunugsewu [ 11 ], the increasing population and various activities can add pressure to the landscapes and groundwater. Moreover, by using principal component analysis (PCA), the the karst groundwater hydrogeochemistry in the Carboniferous Taiyuan Basin have indicated that groundwater has been affected by anthropogenic activities [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the anthropogenic activities factor mainly refers to the agricultural degree, industrial water discharge and groundwater exploitation. According to the study of the eastern part of Gunugsewu [ 11 ], the increasing population and various activities can add pressure to the landscapes and groundwater. Moreover, by using principal component analysis (PCA), the the karst groundwater hydrogeochemistry in the Carboniferous Taiyuan Basin have indicated that groundwater has been affected by anthropogenic activities [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Karst groundwater in general has characteristics that are susceptible to pollution (Budiyanto, 2018, Budiyanto et al, 2020Nanou & Zagana, 2018;Chen et al, 2021). The karst landscape where this research was carried out is naturally capable of escaping water quickly, as well as having a low ability to protect its groundwater against contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia, as an archipelagic country, has numerous vast karst area landscapes, scattered in most of its islands and taking various forms, from archipelagic types such as Raja Ampat and Derawan-Maratua karst areas (Haryono et al, 2018), to the land conical karst type of Karangbolong, Maros, Sangkulirang-Mangkalihat, and Gunung Sewu Karst Area (Hartawan et al, 2020;Haryono et al, 2017). The karst ecosystem in Indonesia and its LULC support millions of people's livelihoods, including in agriculture, settlement, and tourism sectors, while also generating considerable environmental pressure, such as groundwater pollution (Budiyanto et al, 2020). The denser the population, the greater the pressure exerted, as can be clearly seen at the Karst of Gunung Sewu.…”
Section: Introductionmentioning
confidence: 99%